Supported-liquid membrane extraction - Jönsson, Jan Åke; Barri, Thaer (Encyclopedia of Separation Science, web edition, 2007)
Supported-liquid membrane (SLM) extraction is a miniaturized version of liquid–liquid extraction (LLE), involving a hydrophobic membrane containing an organic solvent in the pores. Compared to LLE, it uses microliter-volumes of organic solvents, and provides high enrichment, outstanding clean-up and no emulsion formation. Here, basic principles and technical aspects as well as new developments in the field are discussed
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Analytical Chemistry (S/LTH) (011001004)